Smoking-related Interstitial Lung Disease. Issue 4 (July 2016) - Chakrabarti, Anob M.; Jacobs, Joe; Molyneaux, Philip L.; Devaraj, Anand; Chua, Felix
Abstract : Chronic or heavy smoking can lead to different forms of pathologic remodeling in the airways and distal lung. There is an 8% to 19% prevalence of interstitial lung disease (ILD) in chronic smokers who were unaware that they had a lung disorder. Descriptive pathologic and radiologic analyses have enabled a number of clinical diseases to be identified and grouped within a range of smoking-related ILDs. We review the radiology, pathology, and clinical management of pulmonary Langerhans cell histiocytosis, respiratory bronchiolitis–associated ILD, and desquamative interstitial pneumonia. We discuss the difficulties of classification and also where the new entity of airspace enlargement with fibrosis fits into the current grouping. The prognosis for these conditions is variable depending on the intrinsic behavior of each condition. Smoking cessation is the first-line therapy of choice for any smoking-related ILD, whereas treatment with corticosteroids and other agents forms an important, but occasionally futile, intervention.